HUBUNGAN ANTARA PENINGKATAN KADAR LEKOTRIEN B4 (LTB-4) DENGAN HIPOSELULARITAS SUMSUM TULANG (PENELITIAN PADA ASPIRAT SUMSUM TULANG) - Widjajanto, Edi (Fakultas Kedokteran Universitas Brawijaya, 2005)
ABSTRACT Previous study on human bone marrow culture showed that leukotrien B-4 (LTB-4) which was added to granulocyte-macrophage and erytroid colony, suppressed the growth of colonies. This study assessed the correlation between LTB-4 and marrow cellular. Marrow aspirate which was taken from 60 adult patients (26 men and 34 women) suffering from various haematopoietic problems was examined for amount of LTB-4 and the degree of marrow cellular. ELISA principle was applied for LTB-4 measurement and marrow cellular assessed by counting the member of nucleated cells per cubic-mm of marrow aspirate using microscopic counting chamber principle. Existing difference of the strength of correlation of LTB-4 and marrow cellular was analized using manova and path analysis and expressed as path coefficient.The difference of confounding factors such as gender, age and type of diseases (haematopoitic problems) were controlled and homogenized during statistical analysis using SPSS 10 program. Path coefficient in the multi cellular marrow (n = 60) was – 0.092 (p = 0.495) and path coefficient in hypo cellular marrow (n = 28) was – 0.406 (p = 0.013). This study concludes that the increase of amount of LTB-4 in hypo cellular marrow is associated with the decrease of marrow cellular. Keywords : Leukotrien B-4, Hypocelular marraw, Apoptosis, Hematopoisis